Prevalence of Helminthiasis in Etawa Crossbreed Goat in Kalipuro Sub-District Banyuwangi Regency - khoirul - Arifin; moh. arief ma'ruf; Kusnoto (Journal of Parasite Science (JoPS), 2022)
Etawa crossbreed goat are meat and milk-producing livestock that can adapt to the climate in Indonesia. The barriers to raising goats include the problem of disease which is a direct influence on livestock life. This study aims to determine the prevalence of helminthiasis in Etawa Crossbreed Goat in Kalipuro District, Banyuwangi Regency. The study was conducted in January until February 2019 using 100 fecal samples. The samples examination in was performed the laboratory of Instrument Airlangga University PSDKU in Banyuwangi Prodi of Veterinary Medicine, using native, sedimentation and floatation methods. Data obtained from this study were presented descriptively and analyzed by Chi-Square test. Based on examination results, prevalence of helminthiasis in Etawa Crossbreed Goat was 43 %, which is dominately by Moniezia spp. (17%), Haemonchus spp. (15%), Trichuris spp. (9%), Strongyloides spp. (7%), Trichostrongylus spp. (7%). Furthermore, it was suggested that anthelmintic and inspection of helminthiasis in those area given periodically and continuously. Â